2016
DOI: 10.1159/000448656
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life Impairment in Children and Adults with Vitiligo: A Cross-Sectional Study Based on Dermatology-Specific and Disease-Specific Quality of Life Instruments

Abstract: Background: Vitiligo can negatively affect a patient's quality of life (QoL). A specific questionnaire has been developed and validated in the English language: the vitiligo-specific quality-of-life instrument (VitiQoL). The instrument was translated, culturally adapted and validated into Brazilian Portuguese (VitiQoL-PB). Objective: The aim of this study was to assess the QoL in adult patients through the VitiQoL and Dermatology Life Quality Index (DLQI) and in pediatric patients through the Children's Dermat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
1
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 32 publications
0
30
1
8
Order By: Relevance
“…evaluated QoL of children with vitiligo according to age group. They found that female patients, adolescent patients, and patients with a comorbid psychiatric disease were more likely to have impaired QoL 24 . In our study, no significant difference was found between the QoL scale scores of the groups.…”
Section: Discussioncontrasting
confidence: 73%
“…evaluated QoL of children with vitiligo according to age group. They found that female patients, adolescent patients, and patients with a comorbid psychiatric disease were more likely to have impaired QoL 24 . In our study, no significant difference was found between the QoL scale scores of the groups.…”
Section: Discussioncontrasting
confidence: 73%
“…Among QoL instruments assessing general health, total and/or component scores were most frequently reported for the adult and child versions of the Dermatology Life Quality Index (DLQI, 53 studies) [ 4 , 13 , 14 , 18 , 19 , 22 , 25 , 33 , 35 – 38 , 45 , 64 , 65 , 67 70 , 74 , 77 , 81 – 83 , 87 , 89 , 90 , 92 , 93 , 96 , 99 , 100 , 102 , 104 , 112 , 115 , 119 , 120 , 122 , 123 , 140 , 143 , 144 , 146 , 148 , 151 , 156 , 161 , 162 , 164 – 166 , 168 ], Children’s DLQI (seven studies) [ 24 , 67 , 73 , 101 , 103 , 110 , 152 ], 36-Item Short Form Health Survey (SF-36, eight studies) [ 9 , 82 , 83 , 105 107 , 161 , 162 ], General Health Questionnaire (eight studies) [ 14 , 30 , 65 , 93 ...…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that there was a significant increase in the serum level of cortisol in patients with active vitiligo compared with that in those with either stable vitiligo or a healthy control group 47 . This may be related to high levels of depression and psychogenic stress in vitiligo patients, which can stimulate the secretion of corticotropin-releasing hormone, thus inducing or exacerbating depigmented lesions [48][49][50] . Our findings are consistent with previous reports showing that cortexolone levels gradually decreased as the disease improved.…”
Section: Discussionmentioning
confidence: 99%